2022
DOI: 10.14740/jh921
|View full text |Cite
|
Sign up to set email alerts
|

Leukoerythroblastosis in a Sickle Cell Patient With Pregnancy: An Interesting Peripheral Blood Smear Finding

Abstract: The global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shaken the entire world. The social, health and financial impacts of this pandemic are beyond words. We have learnt a lot about this new disease in a short period of time, but still a long road to go to fully determine its pathogenic effect. The primary target of this virus is angiotensin-converting enzyme 2 (ACE2) receptor, which is prevalent in endothelial cells throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has also been observed that COVID-19 may present atypically in this population, with hepatobiliary manifestations ( 29 ), hematological abnormalities ( 105 , 111 ), and the absence of typical respiratory symptoms ( 33 , 34 , 64 , 82 ). This picture could make it difficult to diagnose the infection and has led some authors to recommend testing individuals with sickle cell disease for COVID-19 even in the absence of classic symptoms ( 64 , 68 , 82 ).…”
Section: Discussionmentioning
confidence: 90%
“…It has also been observed that COVID-19 may present atypically in this population, with hepatobiliary manifestations ( 29 ), hematological abnormalities ( 105 , 111 ), and the absence of typical respiratory symptoms ( 33 , 34 , 64 , 82 ). This picture could make it difficult to diagnose the infection and has led some authors to recommend testing individuals with sickle cell disease for COVID-19 even in the absence of classic symptoms ( 64 , 68 , 82 ).…”
Section: Discussionmentioning
confidence: 90%